2003
DOI: 10.1021/bi0271695
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Redox Instability of Bovine Myoglobin by Adduction with 4-Hydroxy-2-nonenal

Abstract: The redox stability of myoglobin (Mb) is compromised by many factors, including lipid oxidation and its products. 4-Hydroxy-2-nonenal (HNE) is an alpha,beta-unsaturated aldehyde derived from the oxidation of omega-6 polyunsaturated fatty acids and is highly reactive and cytotoxic. Our objective was to study potential binding of HNE to Mb and determine how it affects redox stability. OxyMb (0.15 mM) was incubated with HNE (1 mM) at 4, 25, and 37 degrees C at pH 7.4 or 5.6. Samples were analyzed for MetMb format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
130
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(145 citation statements)
references
References 65 publications
10
130
4
Order By: Relevance
“…3. However, numerous attempts to detect Schiff base formation in various proteins have concluded that the extent to which HNE modifies Lys side chains is insignificant compared with the extent to which His side chains are modified (25,47,(61)(62)(63)(64)(65)(66). Moreover, immunohistochemical studies have shown that anti-HNE-His antibodies bind to amyloid plaques in AD brain tissue (26), but anti-HNE-Lys antibodies do not (36).…”
Section: Discussionmentioning
confidence: 99%
“…3. However, numerous attempts to detect Schiff base formation in various proteins have concluded that the extent to which HNE modifies Lys side chains is insignificant compared with the extent to which His side chains are modified (25,47,(61)(62)(63)(64)(65)(66). Moreover, immunohistochemical studies have shown that anti-HNE-His antibodies bind to amyloid plaques in AD brain tissue (26), but anti-HNE-Lys antibodies do not (36).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid oxidation products could interact with heme pigment, resulting in increased susceptibility of heme iron to oxidation and meat product deterioration (Alderon et al, 2003).…”
Section: Color Parametermentioning
confidence: 99%
“…However, reactive electrophiles also readily react with proteins. Protein modifications by malondialdehyde, 4-hydroxynonenal (HNE) 1 and 4-oxononenal have been characterized on a limited number of proteins by mass spectrometry (MS) (12)(13)(14)(15)(16)(17)(18)(19)(20) and in tissues by antibody-based methods (21)(22)(23)(24)(25)(26). Although relatively little is known about the target selectivity of oxidant-derived lipid electrophiles in complex proteomes, a broader understanding of this phenomenon would provide a basis for understanding mechanisms of oxidant-induced stress and its role in many disease processes.…”
mentioning
confidence: 99%